2018
DOI: 10.1007/s00701-017-3456-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical response to Vim’s thalamic stereotactic radiosurgery for essential tremor is associated with distinctive functional connectivity patterns

Abstract: Brain connectivity measured by resting-state fMRI relates to clinical response after SRS-T. Relevant networks are visual, motor, and attention. Interconnectivity between visual and motor areas is a novel finding, revealing implication in movement sensory guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 44 publications
2
44
0
Order By: Relevance
“…The importance of brain visual areas in tremor pathogenesis has been recently investigated by using a visual task of increasing difficulty to illustrate the impact of visuospatial network in tremor augmentation (Archer et al, 2018). Furthermore, recent series of investigations suggested that structural and functional changes of the visual cortex could be a preoperative predictor of optimum tremor outcome after ablative radiosurgery (Tuleasca et al, 2017(Tuleasca et al, , 2018b(Tuleasca et al, , 2018c.…”
Section: The Tremor Network and Pattern Of Beneficial Dbs Connectivitymentioning
confidence: 99%
“…The importance of brain visual areas in tremor pathogenesis has been recently investigated by using a visual task of increasing difficulty to illustrate the impact of visuospatial network in tremor augmentation (Archer et al, 2018). Furthermore, recent series of investigations suggested that structural and functional changes of the visual cortex could be a preoperative predictor of optimum tremor outcome after ablative radiosurgery (Tuleasca et al, 2017(Tuleasca et al, , 2018b(Tuleasca et al, , 2018c.…”
Section: The Tremor Network and Pattern Of Beneficial Dbs Connectivitymentioning
confidence: 99%
“…Boerwinkle et al 1 have recently suggested that using rs-fMRI might improve outcomes using MRI-guided stereotactic laser ablation for hypothalamic hamartomas. We have demonstrated before how stereotactic radiosurgical thalamotomy for drug-resistant essential tremor (ET) correlates with changes within large-scale brain networks ( Figure 1) [6][7][8][9][10] . Comparison of pre-and post-inventional imaging allowed confirming the role of the ventrointermediate nucleus target region in the tremor network 7,8 .…”
Section: Dear Editormentioning
confidence: 99%
“…5,13,15 Vim radiosurgery (VimRS), as an alternative to standard stereotactic procedures, has 3 major limitations: indirect targeting, no intraoperative confirmation of the Vim target by electrophysiology, and a delayed clinical effect of up to 1 year after the procedure. 7,18,33,37 Tuleasca et al have proposed using resting-state functional MRI (fMRI), [30][31][32]34 a noninvasive neuroimaging technique that can be used to study spontaneous brain activity with minimal patient compliance, to study tremor pathophysiology and improve tremor arrest after VimRS, by using advanced computational techniques. 6 Resting fMRI measures functional connectivity, which has been classically defined as the temporal correlations between spatially remote, statistically independent neurophysiological events distributed across varying neuronal groups and areas.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…The use of resting-state fMRI in observing this network over time might not only allow prediction of clinical response based only on pretherapeutic neuroimaging, 29 but it might also facilitate a better understanding of the radiobiology of radiosurgical intervention and VimRS. 30,32 This work by Tuleasca et al would benefit both from validation in a larger cohort and from the expansion of its usefulness in Vim high-intensity focused ultrasound for tremor which, unlike radiosurgery, has an immediate clinical and radiological effect. 9,10 A collaborative study would require uniformity of clinical assessment, including activities of daily living (from the questionnaire designed by Bain et al), 4 tremor score on the treated hand, 12 and a quality of life questionnaire (QUEST).…”
Section: Imaging Techniquesmentioning
confidence: 99%